1988
DOI: 10.1111/j.1365-2621.1988.tb10222.x
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and Solubility of d‐Limonene Vapor in Cereal Package Liners

Abstract: Studies were carried out on the solubility and permeability of limonene vapor in two cereal package liners. The effect of limonene partial pressure on the permeation rate and permeability coefficient was determined over a concentration range of 0.3 to 7 ppm (wt/v). The equilibrium sorption concentration and solubility coefficient of limonene in the liner films were also determined by a micro-balance gravimetric technique. Data obtained provided information necessary for the estimation of the storage quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 8 publications
1
42
1
1
Order By: Relevance
“…8,14 It was found that the P and D values determined in the present study were higher than those determined by other researchers (Table 4). This may be due to the fact that higher limonene vapour concentration (approximately 21 mg/ml at 25°C) was used in the present study compared with that used by the other research groups (1.5 mg/ml or 0.719 mg/ml).…”
Section: Figure 3 Permeation Profile Of Limonene (21 Mg/ml) Through contrasting
confidence: 76%
See 4 more Smart Citations
“…8,14 It was found that the P and D values determined in the present study were higher than those determined by other researchers (Table 4). This may be due to the fact that higher limonene vapour concentration (approximately 21 mg/ml at 25°C) was used in the present study compared with that used by the other research groups (1.5 mg/ml or 0.719 mg/ml).…”
Section: Figure 3 Permeation Profile Of Limonene (21 Mg/ml) Through contrasting
confidence: 76%
“…In addition, lower permeant concentrations were used in the binary mixture studies, and it has been shown in the literature that permeant concentration has an effect on the permeation data determined. 8,11,15 Therefore, additional studies are required to verify these findings and elucidate the phenomena observed.…”
Section: Permeability Of Limonene and Ethyl Butyrate As Co-permeants mentioning
confidence: 59%
See 3 more Smart Citations